Asignación presupuestaria de fiscalización aduanera y su relación con la recaudación aduanera periodo 2021 – 2023 - Manihuari Alvarez, Denis (2025)
Customs inspection and collection are essential to Peru's economy, as they ensure compliance with international trade regulations and protect the country's economy by preventing smuggling. They are also a crucial source of revenue for the government. Low efficiency in these areas, due to factors such as lack of resources and coordination, generates significant losses in tax revenue. The study aimed to identify the relationship between the customs inspection budget allocation and customs collection at the national level for the period 2021 - 2023, with a quantitative, observational and non-experimental design approach. The results revealed that the accumulated budget allocation reached S/ 139,630,887.00, with a growth of 21.11% in 2022 and a reduction of 6.64% in 2023. This budget was mainly allocated to personnel and social obligations (94% average), while items such as goods, services and infrastructure received less than 2%. On the other hand, customs collection totaled S/ 128,544,813,091.63, peaking in 2022 (+13.61%) and decreasing in 2023 ( 12.06%), with the General Sales Tax (IGV) representing 87% of the annual total. The correlation analysis using Spearman's Rho coefficient showed a weak (0.500) and non-significant (p = 0.667) relationship between budget allocation and collection, indicating independent trajectories. In conclusion, although budget allocation grew moderately, it did not have a direct impact on customs collection, which was more influenced by external factors such as international trade.